Evaluating the impact of the Green Earth Program (Program Bumi Hijau) in Selangor, Malaysia - Man, Norsida (Centre for Extension, Entrepreneurship and Professional Advancement (APEEC), Universiti Putra Malaysia, 2010)
The main purpose of this study is to determine the impact of the Green Earth Program (GEP) in Selangor, specifically in Putrajaya and Kuala Selangor. The data was obtained through questionnaire surveys which distributed to 100 respondents who were selected randomly. To fulfil the objective of this research, the collected data was analysed using descriptive analysis, cross-tabulation and CIPP analysis. The results of the study indicate that high interest in agriculture activities and leisure time was two main factors respondent involve in Green Earth Program. Conversely, lack of time is the main factor contributed to ignorance of Green Earth Program. Apart from that, high commitment and interest toward this program will lead to the success of this program. Government, Non Government Organization (NGO), and media should play an important role in order to develop higher awareness of Green Earth Program to the public.